Sustainable Human Resource Management in Educational Institutions Towards Achieving Sustainable Development Goals (SDG 4) - Susan Febriantina; Ria Rahma Nida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Sustainable Development Goal 4 (SDG 4) emphasizes the provision of inclusive and quality education. However, many educational institutions, especially vocational schools in developing countries, continue to face challenges in implementing sustainable human resource management (Sustainable HRM). This study aims to examine the influence of digital HRM, Green HRM, teacher well-being, inclusivity, and sustainable leadership on Sustainable HRM and its contribution to the achievement of SDG 4 in Jakarta, Indonesia. Methods: This research employed a quantitative explanatory design with a causal approach. Data were collected through a structured questionnaire distributed to 60 teachers from two vocational schools that had adopted digital HRM and sustainability practices. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to test the validity, reliability, and causal relationships among constructs. Findings: The results revealed that sustainable leadership had the strongest positive effect on Sustainable HRM (β = 0.45, p < 0.001), followed by digital HRM (β = 0.35, p < 0.001), Green HRM (β = 0.28, p < 0.001), teacher well-being (β = 0.22, p = 0.004), and inclusivity (β = 0.19, p = 0.013). Moreover, Sustainable HRM significantly influenced the achievement of SDG 4 (β = 0.52, p < 0.001). The model accounted for 67% of the variance in Sustainable HRM and 52% in SDG 4, demonstrating strong explanatory power. Conclusion: The study provides empirical evidence that sustainable leadership, digitalization, and environmentally responsible HRM practices are critical in strengthening Sustainable HRM within vocational schools. In turn, Sustainable HRM substantially contributes to achieving SDG 4 by promoting inclusive and high-quality education. Policy implications highlight the importance of enhancing teacher welfare, inclusivity programs, and Green HRM initiatives to advance educational sustainability in Indonesia.